Usulan Redesain Bak Pencucian Ubi dengan Pendekatan Antropometri Guna Mengurangi Beban Kerja Fisik (Studi Kasus : UD. Rezeki Baru) - Sari, Budi Try; Andriani, Meri; Dewiyana, Dewiyana (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2024)
UD. Rezeki Baru is a micro business engaged in the snack industry. In the production process, workers experience fatigue seen from the activities of workers who complain of pain in the muscles with a bent position. The purpose of this study is to identify the physical workload and provide a proposal for the dimension size of the ergonomic washing tub redesign. The methods used are cardiovascular load to identify physical workload and anthropometric approach to provide proposals for improving the dimension size of ergonomic washing tub redesign. Results and discussion, cardiovascular load in the morning 4 workers experienced "improvement needed" action with each value of 33.7%, 50%, 31.7%, 52.6% and 1 worker experienced "work in a short time" action with a value of 70.5% while in the afternoon 1 worker got a percentage of 57.6% with a classification of "improvement needed", 3 workers got a classification of "work in a short time" with a value of 78.3% each,  63.4%, 68.3% and 1 worker received a classification of "urgent action needed" with a percentage of 84.6% then measured 3 dimensions of the worker's body, namely Standing Elbow Height, Elbow Length to Fingertips and Hand Stretch, data adequacy test stated sufficient data, data uniformity test stated all data was uniform, data normality test with SPSS software stated normal distributed data with P50 and P95 percentiles. The conclusion of cardiovascular load received by workers received an average value of 47.7% with a classification of "improvement needed" in the morning while in the afternoon received an average value of 70.44% with a classification of "work in a short time". The redesigned size of the ergonomic sweet potato washer tub is 106.4 cm high, 179.5 cm long and wide, and 48.64 cm deep with a volume of 1567.19 liter.